DETERMINATION OF PRELIMINARY OPERATING POWER DENSITY RANGES FOR SOME LASER TECHNOLOGICAL PROCESSES ON AISI 316 STAINLESS STEEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Determination of preliminary operating intervals of power density is the first step in optimizing laser technological processes for AISI 316 stainless steel. The study focuses on the laser technological processes of laser marking, laser cutting, and laser welding. Based on the heat conduction equation and the heat balance equation, calculations were performed to determine the critical power density of melting and vaporization at various speeds for the three processes, taking into account the optical and thermo-physical parameters of the material. The results were graphically presented, analyzed, and summarized. Preliminary operating intervals were determined for laser marking through oxidation, melting, and vaporization, as well as for laser cutting and laser welding at different speeds. Our experimental results, along with results from other authors, showed good agreement with the theoretically defined power density intervals for all three technological processes.